Inhalation toxicity of (1→3)-β-D glucan: recent advances - Birgitta Fogelmark; Margareta Sjöstrand; David Williams; Ragnar Rylander (Mediators of Inflammation)
To investigate the effects of (1→3)-β-D-glucan after inhalation, animals were exposed to different forms of glucan and the number of lung lavage cells was determined 24 h after exposure. None of the different forms assayed caused any increase in cell numbers. In animals exposed to endotoxin, all types of cells were increased after 24 h. A simultaneous exposure to curdlan reduced this increase in a dose-related fashion. The results suggest that (1→3)-β-D-glucan-related acute injury to the lung is induced by mechanisms other than those induced by inflammagenic agents such as endotoxin.